Short- and long-term outcomes of totally robotic versus robotic-assisted radical distal gastrectomy for advanced gastric cancer: a mono-institution retrospective study - Luo, Rui (World J Surg Oncol, 2019)
PURPOSE: By comparing short- and long-term outcomes following totally robotic radical distal gastrectomy (TRDG) and robotic-assisted radical distal gastrectomy (RADG), we aimed to assess in which modus operandi patients will benefit more. METHODS: From January 2015 to May 2019, we included 332 patients undergone RADG (237) and TRDG (95). Based on the propensity score matching (PSM), inclusion and exclusion criteria, 246 patients were finally included in the propensity score-matched cohort including RADG group (164) and TRDG group (82). We then compared the short- and long-term outcomes following both groups. RESULTS: Propensity score-matched cohort revealed no significant differences in both groups. Intra-abdominal bleeding, time to pass flatus, postoperative activity time, length of incision hospital stays, and stress response were significantly less in TRDG group than in RADG group. We observed 30 complications in RADG group while 13 complications in TRDG group. There were no significant differences in TRDG group and RADG group in terms of operation time, time for anastomosis, proximal resection, distal resection margin, number of lymph node resection, and total hospitalization cost. Both 3-year overall survival and 3-year disease-free survival were comparable in both groups. CONCLUSIONS: TRDG is a safe and feasible modus operandi profiting from short- and long-term outcomes compared with RADG. As surgeons improving their professional skills, TRDG could serve as the standard procedure for distal locally advanced gastric cancer with D2 lymphadenectomy.